Verbal Representation Analysis of Meaning in Gojek and Grab TV Commercials - Mutia Resha Gucen; Hamzah Hamzah (English Language and Literature, 2020)
AbstractThis study aims to examine the difference in meaning in verbal analysis in Gojek and Grab advertisements. The purpose of this research is to find the difference in meaning in verbal analysis at the level of Systemic Functional Linguistics, namely ideational, interpersonal, and textual metafunction. The data were analyzed using the theory of Systemic Functional Linguistics Halliday (2006). The data is the utterances contained in the Gojek and Grab advertising videos. The method of this research uses descriptive qualitative research. The results showed that there were some differences in the two advertisements in using Systemic Functional Linguistics, namely mood analysis, attitude, modality, graduation, and theme. The five differences are dominated by Gojek advertisements.Key words: systemic functional linguistics, semiotics, advertisementAbstarkPenelitian ini bertujuan untuk mengkaji perbedaan makna dalam analisis verbal pada iklan Gojek dan Grab. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan makna dalam analisis verbal pada tingkat Systemic Functional Linguistics yaitu ideational, interpersonal, dan textual metafunction. Data dianalisis dengan menggunakan theory Systemic Functional Linguistics Halliday (2006) dengan pedekatan semiotik. Datanya adalah ujaran-ujaran yang terdapat didalam vidio iklan Gojek dan Grab. Metode dari penelitian ini menggunakan descriptive qualitative research. Hasil penelitian menunjukkan bahwa terdapat beberapa perbedaan dalam kedua iklan dalam menggunakan Systemic Functional Linguistics, yaitu mood analysis, attitude, modality, graduation, dan theme. Lima perbedaan itu didominasi oleh iklan Gojek.